Evaluation of a minor eye conditions scheme delivered by community optometrists. Issue 8 (10th August 2016) - Konstantakopoulou, E; Edgar, D F; Harper, R A; Baker, H; Sutton, M; Janikoun, S; Larkin, G; Lawrenson, J G
Abstract : Background: The establishment of minor eye conditions schemes (MECS) within community optometric practices provides a mechanism for the timely assessment of patients presenting with a range of acute eye conditions. This has the potential to reduce waiting times and avoid unnecessary referrals to hospital eye services (HES). Objective: To evaluate the clinical effectiveness, impact on hospital attendances and patient satisfaction with a minor eye service provided by community optometrists. Methods: Activity and outcome data were collected for 12 months in the Lambeth and Lewisham MECS. A patient satisfaction questionnaire was given to patients at the end of their MECS appointment. A retrospective difference-in-differences analysis of hospital activity compared changes in the volume of referrals by general practitioners (GPs) from a period before (April 2011–March 2013) to after (April 2013–March 2015) the introduction of the scheme in Lambeth and Lewisham relative to a neighbouring area (Southwark) where the scheme had not been commissioned. Appropriateness of case management was assessed by consensus using clinical members of the research team. Results: A total of 2123 patients accessed the scheme. Approximately two-thirds of patients (67.5%) were referred by their GP. The commonest reasons for patients attending for a MECS assessment were 'red eye' (36.7% of patients), 'painful white eye' (11.1%) and 'flashes and floaters' (10.2%). A total of 64.1% of patients were managed in optometric practice and 18.9% were referred to the HES; of these, 89.2% had been appropriately referred. First attendances to HES referred by GPs reduced by 26.8% (95% CI −40.5% to −13.1%) in Lambeth and Lewisham compared to Southwark. Conclusions: The Lambeth and Lewisham MECS demonstrates clinical effectiveness, reduction in hospital attendances and high patient satisfaction and represents a successful collaboration between commissioners, local HES units and primary healthcare providers.